2013
DOI: 10.3389/fpls.2013.00480
|View full text |Cite
|
Sign up to set email alerts
|

The GIP gamma-tubulin complex-associated proteins are involved in nuclear architecture in Arabidopsis thaliana

Abstract: During interphase, the microtubular cytoskeleton of cycling plant cells is organized in both cortical and perinuclear arrays. Perinuclear microtubules (MTs) are nucleated from γ-Tubulin Complexes (γ-TuCs) located at the surface of the nucleus. The molecular mechanisms of γ-TuC association to the nuclear envelope (NE) are currently unknown. The γ-TuC Protein 3 (GCP3)-Interacting Protein 1 (GIP1) is the smallest γ-TuC component identified so far. AtGIP1 and its homologous protein AtGIP2 participate in the locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(107 citation statements)
references
References 69 publications
3
104
0
Order By: Relevance
“…26 Interestingly, the minimal domain of interaction of TSK was partly overlapping with that of GIP1 in the C-terminal region of TSA1. 6,9 These data argue for a spatiotemporal regulation of GIP1, TSA1 and MGO3 interactions to properly ensure centromere cohesion. In addition, in tsk mutants, a stabilization of TSA1 was observed without any changes in the TSA1 transcript level, 16 contrary to mgo3 in which we showed that TSA1 was upregulated (3 to 4 times, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Interestingly, the minimal domain of interaction of TSK was partly overlapping with that of GIP1 in the C-terminal region of TSA1. 6,9 These data argue for a spatiotemporal regulation of GIP1, TSA1 and MGO3 interactions to properly ensure centromere cohesion. In addition, in tsk mutants, a stabilization of TSA1 was observed without any changes in the TSA1 transcript level, 16 contrary to mgo3 in which we showed that TSA1 was upregulated (3 to 4 times, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, we demonstrated that GIPs, initially found as regulators of the recruitment of microtubule-nucleation complexes, were also key players in the regulation of the nuclear architecture. 5,6 GIPs located on both sides of the Nuclear Envelope (NE) play a critical role in the maintenance of centromeric cohesion in the nuclei of cycling cells studied in Arabidopsis root meristems. 7,8 Interestingly, GIPs were identified as partners of TSA1 6 which was first described as TONSOKU (TSK)-associating protein1.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that γ-tubulin complex (γ-TuC) components are associated with the nuclear envelope and that microtubule growth can initiate on the nuclear surface (Batzenschlager et al, 2013). Proteins involved are γ-TuC protein 3 (GCP3) and GCP3-interacting protein (GIP) (Janski et al, 2012;Batzenschlager et al, 2015).…”
Section: Mitosis and Meiosismentioning
confidence: 99%
“…Proteins involved are γ-TuC protein 3 (GCP3) and GCP3-interacting protein (GIP) (Janski et al, 2012;Batzenschlager et al, 2015). GCP3 interacts with GIP, and GIP in turn interacts with TonSoku-associating protein 1 (TSA1), a TMD protein associated with the nuclear envelope (Batzenschlager et al, 2013). It could therefore be tested whether members of the WIP and/ or WIT families interact with any components of the plant γ-TuC that are associated with the nuclear envelope, such as GIP or GCP3 (Fig.…”
Section: Mitosis and Meiosismentioning
confidence: 99%
“…They also point to divergences with ARK1 having a broad function during the entire root hair developmental program and AGD1 being more specifically involved in the early stages of root hair initiation and tip growth. Batzenschlager et al (2013) bring us into a functional study suggesting that the Arabidopsis γ-tubulin complex (γ-TuC) components GCP3-interacting protein1 (GIP1) and GIP2 are key determinants of nuclear shaping and nuclear envelope organization. The authors also report the identification of a novel and direct partner of AtGIP1, namely AtTSA1, which partially colocalizes with AtGIP1 at the nuclear envelope.…”
Section: Trafficking On the Cytoskeleton Toward The Plasma Membrane Amentioning
confidence: 99%